Picking up flexible pieces out of a bundle. - Doulgeri, Z.
The paper describes a robotic-arm gripper with soft-tipped fingers to perform human-like grasps of flexible material pieces out of an unordered bundle. The primary purpose is to achieve the stability and robustness of a human-like grasp with a simple and cost-effective gripper. The work has been stimulated by the handling problem present in the fur-tanning industry
Keywords: Automatic fur handling; Computer vision; Flexible material grasping; Gripper; Human-like grasp; Materials handling system; Robotic-arm gripper; Stability